Ozonized oil use in wounds: Case report - Ricco, Flavia (Pubvet, 2022)
The use of ozonized oil has been shown to be a very efficient technique in veterinary medicine thanks to its oxidizing power, being very efficient in bacterial, fungal, viral diseases, subcutaneous and cutaneous lesions, in addition to its analgesic and anti-inflammatory potential. This article aims to analyze the use of ozonized oil in the treatment of wounds in dogs. Therefore, a literature report of the case of a 9-year-old female dog who had wounds and was treated with the use of ozonized oil. It was possible to observe positive results without causing discomfort to the animal.
Keywords: Wounds; ozonized oil; treatment